Power Oscillation Damping Control using Robust Coordinated Smart Devices - Tumiran Tumiran; Cuk Supriyadi Ali Nandar; Sarjiya Sarjiya (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
The lack of damping of the electromechanical oscillation modes usually causes severe problems of low frequency oscillations in interconnected power systems. In the extreme operating conditions, PSS may fail to damp power oscillation. This paper presents a robust coordinated design of power system stabilizer (PSS) and thyristor controlled series capacitor (TCSC) to damp power oscillation in an interconnected power system. The inverse additive perturbation is applied to represent unstructured uncertainties in the power system such as variations of system parameters, system generating and loading conditions. In addition, genetic algorithm is employed to search a robust tuning to the controller parameters of both PSS and TCSC simultaneously. Simulation studies have been done in a single machine infinite bus system to confirm that the performance and robustness of the proposed controller are superior to that of the conventional controller.